1979
DOI: 10.1021/ac50048a003
|View full text |Cite
|
Sign up to set email alerts
|

Laser enhanced ionization spectrometry in analytical flames

Abstract: A new variety of analytical atomic flame spectrometry called laser enhanced ionization (LEI) has been developed. The method relies on the enhanced rate of thermal ionization of the analyte element following photoexcitation with a dye laser tuned to an appropriate transition wavelength. This enhanced Ionization rate can be electrically measured directly in the flame, and therefore no optical detection system is required.Detection limits have been measured for 18 elements, showing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 15 publications
4
45
1
Order By: Relevance
“…(1) is accommodated in eqn. (3) in the rate constant hi = koPt (4) where the collision rate of X and A species, kg, obviously depends on the number density of X, as well as other factors.…”
Section: Making Ionsmentioning
confidence: 99%
“…(1) is accommodated in eqn. (3) in the rate constant hi = koPt (4) where the collision rate of X and A species, kg, obviously depends on the number density of X, as well as other factors.…”
Section: Making Ionsmentioning
confidence: 99%
“…It has been demonstrated that the acoustic wave measurement can normalize the atomic emission signal generated from the laser plume so that the influence from laser power fluctuations and matrix effects is minimized (15). Another characteristic feature of the laser plasma is that ions can be formed through either thermal ionization (16,17) or laser-induced ionization processes (18)(19)(20)(21)(22). The thermal ionization process under these experimental conditions only induces very small amounts of atomic ions.…”
Section: Introductionmentioning
confidence: 99%
“…These highly excited atoms or molecules can be ionized subsequently by collisions or by absorbing more photons to reach the ionization continuum. The first process has been referred to as laser-enhanced ionization (LEI) (18)(19)(20). LEI combined with an analytical flame, which serves as an atom reservoir, has been used for trace elemental analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The outstanding performance of LEI in trace element analysis has been demonstrated in a number of reports previously, both in flames [1,3,4,11,12,19,21,22,28] and in furnaces [-17, 25]. For flame-LEI, detection limits in the 0.001-1 ng/ml range in aqueous solutions are readily obtained with one-step excitations of elements with low or moderate ionization potentials.…”
Section: Detection Limits and Sensitivitiesmentioning
confidence: 93%